2019
DOI: 10.1590/s2175-97902019000218129
|View full text |Cite
|
Sign up to set email alerts
|

Application of quality by design approach in RP-HPLC method development for simultaneous estimation of saxagliptin and dapagliflozin in tablet dosage form

Abstract: A simple, sensitive, precise, accurate and robust high performance liquid chromatographic method has been developed for simultaneous estimation of saxagliptin (SAXA) and dapagliflozin (DAPA) in pharmaceutical formulation. Design of experiments (DoE) was applied for multivariate optimization of the experimental conditions of RP-HPLC method. Risk assessment was performed to identify the critical method parameters. Three independent factors; mobile phase composition, flow rate and column temperature were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The model was also validated by ANOVA using Design Expert software. The predicted R-Squared values of retention time of TOR (Y 1 ) and EPL (Y 2 ) were in reasonable agreement with adjusted R-Squared values i.e., the difference is less than 0.2, as reported by other authors (Awotwe-Otoo et al, 2012;Gundala et al, 2019). A negative predicted R-Squared value for resolution (Y 3 ) implies that the overall mean may be a better predictor of the response than the current model.…”
Section: Qbd Assisted Methods Developmentsupporting
confidence: 79%
“…The model was also validated by ANOVA using Design Expert software. The predicted R-Squared values of retention time of TOR (Y 1 ) and EPL (Y 2 ) were in reasonable agreement with adjusted R-Squared values i.e., the difference is less than 0.2, as reported by other authors (Awotwe-Otoo et al, 2012;Gundala et al, 2019). A negative predicted R-Squared value for resolution (Y 3 ) implies that the overall mean may be a better predictor of the response than the current model.…”
Section: Qbd Assisted Methods Developmentsupporting
confidence: 79%
“…Present method was found to be cost-effective owing to utilization of low % (26%) organic mobile phase than latest literature [10]. The analytical run duration for the proposed method is short (6 min); hence, this method was rapid and superior than literature methods [8,[11][12][13]. When compared with previous HPLC reports [14][15][16][17][18] for this drug combination, the proposed method has advantages such as high resolution (7.3) and wide linearity range (0.1-150 μg/mL, 0.2-300 μg/mL).…”
Section: Methods Comparison With Literature Methodsmentioning
confidence: 89%
“…Literature survey revealed that there were few reports published on the simultaneous quantification of dapagliflozin and saxagliptin using UV [8], HPTLC [9], HPLC [10][11][12][13][14][15][16][17][18], and LC-MS [19,20] techniques in bulk drug and pharmaceutical dosage forms. Few methods were reported for analysis of dapagliflozin and saxagliptin separately [21][22][23][24] and in combination with other drugs [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…(Vogt and Kord 2011;Peraman et al 2015b; Das and Maity 2017) As a result, using Quality by Design concepts towards the construction of analytical methods has become rather prevalent in order to achieve high robustness and superior method performance. (Monks et al 2012) In recent times, many analytical methods for single drug estimation (Alruwaili 2021;Jena et al 2021;Patel et al 2021;Srujani et al 2021;Wadhwa et al 2021) and simultaneous quantification (Gundala et al 2019;Saurabh Chaudhari et al 2022) have been developed using AQbD method. Analytical quality by design refers to the systematic and scientific creation and optimization of analytical procedures.…”
Section: Methods Development Incorporating Qbdmentioning
confidence: 99%